ответ:1-oе фото
1)x²-2x-35 2)3x²+16x+5 3)x²-13x+40
x²-2x-35=0 3x²+16x+5=0 x²-13x+40=0
D=4+4*35=144 D=256-4*3*5=196 D=169-4*40=9
x1=(2+12):2=7 x1=(-16+14):6=5 x1=(13+3):2=8
x2=(2-12):2=-5 x2=(-16-14):6=0,3333333 x2=(13-3):2=5
4)6x²+x-1
6x²+x-1=0
D=1+4*6*1=25
x1=(-1+5):12=0,3333333
x2=(-1-5):12=-0,5
а+3\а+2 = 2\x - 5\x(a+2)
a+3\a+2 * x = 2\x * (a+2) - 5\ x(a+2)
x(a+3)\(a+2)= 2(a+2) - 5\ x(a+2)
ax + 3x\ x(a+2) = 2a+4\ x(a+2)-5\x(a+2)
ax+3x -(2a+4) + 5\ x(a+2)=0
ax+3x-2a-4+5\ x(a+2) =0
ax+3x-2a+1\ x(a+2)=0
(ax-2a)+(3x+1)\ x(a+2)=0
...